Analisis Perkembangan Fisik Motorik Anak di TK Taman Harapan - Anti Pebriani Syahpitri; Fitra Handayani; Siti Halisah; Wildani Wildani; Fauziah Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to observe and monitor the physical-motor development of early childhood at Taman Harapan Kindergarten. Children's physical development is in the form of biological growth, namely muscle growth, brain growth, and bone growth. The importance of educators and parents in sharpening and monitoring children's physical-motor development so that children are independent in doing anything. The location of this research was conducted at Taman Harapan Kindergarten which is domiciled on Jl Ibrahim Umar No. 8, Medan Perjuangan District in a vulnerable time on 05-07 October 2022 starting at 08.00 WIB until finished. In data collection techniques, researchers use direct and indirect observation techniques and documentation. The results of this study indicated that the physical-motor development of all children in Taman Harapan Kindergarten grew well because the teaching staff carried out various activities to improve the physical-motor development in the process. Keywords: Development, Physical-Motoric, Early Childhood